'If I don't take care of myself, who will?' Self-caring subjects in Oaxaca's mutual-aid groups. Issue 4 (1st October 2020) - Montesi, Laura
Abstract: Based on seven months of ethnographic fieldwork in two urban health centres in Oaxaca City, Mexico, this paper analyses the ways in which underprivileged middle-aged and older female patients experience and transform grupos de ayuda mutua (GAMs), or mutual-aid groups, a public health programme aimed at improving chronic patients' adherence to their biomedical treatments. GAMs work as 'technologies of the self' within the context of the Mexican neoliberal regime and patients are urged to be self-responsible. GAM members regard such urging favourably and act according to their broader understandings of life, which they see as a lucha (struggle) that requires cuidarse (a polysemic verb alluding to self-care for self-preservation) and hard work in a structurally unequal place characterised by precarity and social unrest. This seemingly rugged individualism is converted into microlevel collaboration through culturally distinctive Oaxacan practices of mutual help. By exploring the playful ways these women participate in GAMs, this paper shows how biomedical settings can be repurposed as spaces of socialisation and wellbeing for older women living in vulnerable conditions.